O USO DE RECIFES ARTIFICIAIS COMO INSTRUMENTO DE SUPORTE À PESCA EM REGIÕES PRODUTORAS DE PETRÓLEO OFFSHORE - Bastos, Luciana de Figueiredo (2005)
This study proposes to present the founded challenges in one process to install Artificial Reefs in Brazil, experience where the author verified that to implement a National Politics which the application artificial structures interacts with the environment, it will be necessary a deep analysis of its importance for sustainability. In this sense, the artificial structures importance should be observed to the maintenance of physical integrity on the coastal line, to recover degraded areas close to the coast, the enrichment and induction of the bioproduction in the continental platform and growth of traditional economical activities as the craft fishing, among others. This dissertation will present a Case Study, in Campos' Basin, where the installation of an Artificial Reef Pilot Project consisted on occupation of the little productive underwater soil and degraded, with disactivated structures of petroleum s industry, aiming at constituting habitats for different species of fish and crustaceans and generating socioeconomic benefits for the craft fishing. Based on all information, the work intends to recommend the use of the strategy adopted by the Brazilian Petroleum S.A. - PETROBRAS Business Unit of Campos' Basin (UN-BC) - Macaé / RJ, developed to make possible the authorization for the Artificial Reefs Installation in accordance with all criterions, not regulated yet, to be in agreement with the Environmental Organs and other involved entities. The presentation includes the legal and institutional aspects, related to the preservation of the underwater environment and to the national proposals, which guide until the regulation of the Artificial Reefs installation. It will still stand out the international recommendations that includes the construction of artificial reefs, in agreement with the proposed alternatives, regarding the decommissioning structures of petroleum production. In this scenery, it was established as a tool of work several bibliographical studies with varied approaches on the subject.